PROSES PELATIHAN TARI NGILO MENGGUNAKAN METODE “DEK, DEG, SER” PADA KELAS C DI SANGGAR PADMA GAYATRI DESA KESAMBEN KABUPATEN MALANG - RismaAyu Susilowati; Ika Wahyu Widyawati (Institut Seni Indonesia Surakarta, 2026)
Dance training in studios as a form of non-formal education requires appropriate methods to ensure an effective learning process. Padma Gayatri Dance Studio applies a specific method in Ngilo Dance training for class C as an effort to improve training outcomes. This study aims to describe the process of Ngilo Dance training using the “Dek, Deg, Ser” method in Class C at Padma Gayatri Dance Studio. This research employs a descriptive qualitative approach. Data were collected through observation, intrerviews, and documentation involving instructors, Class C students, Peer tutors, parents, and dance experts. Data analysis used the interactive model Miles dan Huberman with source and rechnique triangulation. The results show that the training is conducted systematically through the stages of opening, material delivery, warm-up, core practice, evaluation, and reflection. The “Dek, Deg, Ser” method, combined with demonstration, Drill, peer tutoring, and open space training, effectiely improves technical mastery, movement memorization, focus, and students discipline. The findings contribute to training practice and serve as a reference for dance instructors.